MAFHÛM AL-RÛḤ (AL-ÂTMAN) FÎ AL-NUṢÛṢ AL-HINDÛSIYYAH - Mishbah Khoiruddin Zuhri (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
The spirit (al-Âtman) is a Hindu metaphysical subject. It is spritual existence, intangible by the senses, and abstracted from material physical matters. It is not subject to natural laws, which go beyond the limits of nature. It is the life force of living beings, and a spiritual substance that is not perceived by ordinary means. It is the source of life and movement in all assets.  Âtman is immortal and inexhaustible.